Pseudospin Symmetry of the Position-Dependent Mass Dirac Equation for the Hulthén Potential and Yukawa Tensor Interaction - A.N. Ikot; C.N. Isonguyo; J.D. Olisa; H.P. Obong (PPIKSN-BATAN, 2014)
This paper presents approximate analytical solutions of the Dirac equation for the Hulthén potential with position-dependent mass within the framework of pseudospin symmetry limit using the Nikiforov-Uvarov method. The results showed the relativistic energy spectrum and the corresponding un-normalized wave function expressed in terms of the Jacobi polynomials.Received: 30 September 2014; Revised: 29 December 2014: 31 December 2014